Pengaruh Penggunaan Augmented Reality Virtual Try on Terhadap Keputusan Pembelian Kosmetik X: Penelitian - Laras Safitri Balqis; Nurul Hidayah; Lilis Jubaedah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the effect of Augmented Reality (AR) Virtual Try On on purchase decisions of L’Oréal Paris cosmetic products in Shopee Indonesia e-commerce platform. This research employs a quantitative method with a survey approach. Data were collected through questinonnaires. The sampling technique used was purposive sampling. The results indicate that the use of AR Virtual Try On has a positive and significant effect on purchase decisions. The findings show that AR Virtual Try On feature provides an interactive shopping experience and helps consumers evaluate cosmetic products more accurately, thereby increasing confidence and purchase decisions.